Imperialism, immigration and identity : deterministic and symbolic violence in the southeast Asian American novel. - He, Tanya Siying. (2011)
The main aim of this paper is to join the long-term debate within the field of Asian American studies, on how Asia is defined in the Asian-American context as the field continually renews itself in response to changing patterns of Asian immigration to the United States, by focusing on Southeast Asian-American literature. This is especially relevant in today’s global climate of mass consumerism, ease of travel, and transnational activities that bring about greater diversity in the Asian American population and community. Early anthologies and critiques tend to privilege writers from Chinese, Japanese and Filipino Asian groups, and with the most recent wave of Asian migrants of Southeast Asian descent, there is a need for a renewed interest in Southeast Asian-American literature so as to modernise and refine perspectives on Asian diasporas, transnationalism, immigration and assimilation, cultural, social and economic alienation, as well as marginalization and the western gaze.